Enhancing Employee Performance through Quality Work Life: The Mediating Roles of Job Satisfaction and Organizational Citizenship Behavior in Riau’s Government-Owned Credit Insurance Sector - Pahlawan, Ryan; Indarti, Sri; Savitri, Enni; Setiawan, Deny (Journal of Ecohumanism, 2024)
This study investigates the impact of Quality of Work Life (QWL) on employee performance, with a focus on the mediating effects of Job Satisfaction (JS) and Organizational Citizenship Behavior (OCB) in government-owned credit insurance companies in Riau Province. Based on quantitative causality research with a sample of 309 employees, this study employs Structural Equation Modeling (SEM) to examine how QWL directly and indirectly influences performance. Key findings reveal that QWL positively impacts both job satisfaction and OCB, which in turn significantly enhance employee performance. These insights underscore the importance of fostering a supportive work environment to improve organizational outcomes, particularly in sectors reliant on high employee engagement and performance. The implications for managerial practice and potential areas for future research are also discussed.